Histopathological Examination Of Thyroid Tissue In Patients With Thyroid Disorders In Iraq (Journal of Pharmaceutical Negative Results, 2020)
Thyroid disorders are prevalent worldwide, with significant variations in histopathological findings across different populations. This study aimed to evaluate the histopathological features of thyroid tissue in Iraqi patients with thyroid disorders. A retrospective analysis was conducted on 300 thyroidectomy specimens obtained from patients diagnosed with thyroid disorders between January 2018 and December 2022. The specimens were examined for histopathological features, including nodular hyperplasia, thyroiditis, follicular adenoma, papillary carcinoma, and follicular carcinoma. The results revealed that nodular hyperplasia was the most common finding (45%), followed by papillary carcinoma (25%), thyroiditis (15%), follicular adenoma (10%), and follicular carcinoma (5%). The study highlights the importance of histopathological examination in accurately diagnosing and managing thyroid disorders in Iraq. The findings provide valuable insights into the prevalence and distribution of thyroid pathologies in the Iraqi population, which can aid in the development of targeted diagnostic and therapeutic strategies.